1970
DOI: 10.1073/pnas.65.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Activity in the Spinal Cord of the Chick Embryo, in situ

Abstract: Abstract. Unit electrical activity was recorded from single neurons in the lumbo-sacral spinal cord of 15-, 17-, and l9-day chick embryos, in situ. The dorsal columns showed relatively continuous single-unit activity. Below this lies an area of relative quiet 100-200,t deep. The ventral two thirds of the cord was the most active region, being characterized by polyneuronal bursts and intermittently active single units.The origin of motility of the chick embryo has been the subject of considerable conjecture. Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This profile appears to be rooted in early development through an orderly addition of neurons to the developing network (47). In chicken embryos, neuronal activity is higher in the ventral two thirds of the spinal cord than in the dorsal region (48). Taken together these studies suggest that the patterning of excitability along the dorsoventral axis of the developing spinal cord is highly conserved and relevant for proper spinal cord development.…”
Section: Discussionmentioning
confidence: 52%
“…This profile appears to be rooted in early development through an orderly addition of neurons to the developing network (47). In chicken embryos, neuronal activity is higher in the ventral two thirds of the spinal cord than in the dorsal region (48). Taken together these studies suggest that the patterning of excitability along the dorsoventral axis of the developing spinal cord is highly conserved and relevant for proper spinal cord development.…”
Section: Discussionmentioning
confidence: 52%
“…To address this question, we focused on two distinct structures of the mouse CNS expressing immature rhythmic activity at different developmental times, namely the embryonic hindbrain-spinal cord and the postnatal cortex. Indeed, immature rhythmic activity in the former structures is largely expressed at embryonic stages (Provine et al, 1970;O'Donovan, 1989;Nishimaru et al, 1996;Hanson and Landmesser, 2003;Yvert et al, 2004;Hunt et al, 2005;Thoby-Brisson et al, 2005;MomoseSato et al, 2007), while cortical networks express major rhythms during the first postnatal week (Yuste et al, 1992;Khazipov et al, 2004;Allène et al, 2008). In both cases, we found that the emergence of activity was strictly dependent upon the movement of artificial CSF (aCSF) around the tissue.…”
Section: Introductionmentioning
confidence: 66%
“…Yet, until the sophistication of our current analytical techniques is improved, such questions will remain unanswered for the chick embryo. That such sophistication may not be long in coming is suggested by the recent reports that electrophysiological recordings can now be made from the spinal cord of young chick embryos (Provine, Sharma, Sandel & Hamburger, 1970).…”
Section: Discussionmentioning
confidence: 99%